Impact of COVID-19 outbreak on cancer immunotherapy in Italy: a survey of young oncologists. Issue 2 (15th October 2020) - Ottaviano, Margaret; Curvietto, Marcello; Rescigno, Pasquale; Tortora, Marianna; Palmieri, Giovannella; Giannarelli, Diana; Aieta, Michele; Assalone, Pasquale; Attademo, Laura; Avallone, Antonio; Bloise, Francesco; Bosso, Davide; et al.
Abstract : Background: The coronavirus disease 2019 (COVID-19) pandemic has overwhelmed the health systems worldwide. Data regarding the impact of COVID-19 on cancer patients (CPs) undergoing or candidate for immune checkpoint inhibitors (ICIs) are lacking. We depicted the practice and adaptations in the management of patients with solid tumors eligible or receiving ICIs during the COVID-19 pandemic, with a special focus on Campania region. Methods: This survey (25 questions), promoted by the young section of SCITO (Società Campana di ImmunoTerapia Oncologica) Group, was circulated among Italian young oncologists practicing in regions variously affected by the pandemic: high (group 1), medium (group 2) and low (group 3) prevalence of SARS-CoV-2–positive patients. For Campania region, the physician responders were split into those working in cancer centers (CC), university hospitals (UH) and general hospitals (GH). Percentages of agreement, among High (H) versus Medium (M) and versus Low (L) group for Italy and among CC, UH and GH for Campania region, were compared by using Fisher's exact tests for dichotomous answers and χ 2 test for trends relative to the questions with 3 or more options. Results: This is the first Italian study to investigate the COVID-19 impact on cancer immunotherapy, unique in its type and very clear in the results. The COVID-19 pandemic seemed not to affect the standard practice in the prescription and delivery of ICIs in Italy. Telemedicine was widely used. There was high consensus to interrupt immunotherapy in SARS-CoV-2–positive patients and to adopt ICIs with longer schedule interval. The majority of the responders tended not to delay the start of ICIs; there were no changes in supportive treatments, but some of the physicians opted for delaying surgeries (if part of patients' planned treatment approach). The results from responders in Campania did not differ significantly from the national ones. Conclusion: Our study highlights the efforts of Italian oncologists to maintain high standards of care for CPs treated with ICIs, regardless the regional prevalence of COVID-19, suggesting the adoption of similar solutions. Research on patients treated with ICIs and experiencing COVID-19 will clarify the safety profile to continue the treatments, thus informing on the most appropriate clinical conducts.